Taking Action: Transforming Athens' Urban Landscapes - Kling, Norbert; Roidis, Tasos; Michaeli, Mark (Jovis Verlag GmbH, 2023)
English edition with Greek abstracts / Englische Ausgabe mit griechischen Abstracts Taking Action brings into focus the sustainable design of urban transformation and the preparation of densely-structured urban spaces for future challenges.